2012
DOI: 10.1016/j.yfrne.2012.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Rapid control of male typical behaviors by brain-derived estrogens

Abstract: Beside their genomic mode of action, estrogens also activate a variety of cellular signaling pathways through non-genomic mechanisms. Until recently, little was known regarding the functional significance of such actions in males and the mechanism that control local estrogen concentration with a spatial and time resolution compatible with these non-genomic actions had rarely been examined. Here, we review evidence that estrogens rapidly modulate a variety of behaviors in male vertebrates. Then, we present in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
75
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(78 citation statements)
references
References 289 publications
(436 reference statements)
2
75
0
1
Order By: Relevance
“…The transient nature of the T administration mimicked natural-occurring pulses seen in intersexual rodent social encounters (James et al, 2006;Macrides et al, 1975) and in the current study, this pulse inhibited acoustic communication with a novel female within 30 min, which is considered rapid for steroid hormones (Cornil et al, 2012;Remage Healy, 2012;Wu et al, 2001). The precise mechanism through which T is acting cannot be determined in the present study, but recent research has identified intriguing rapid effects of steroid hormones achieved by non-genomic mechanisms (Cornil et al, 2013;Mangiamele and Thompson, 2012), including effects on acoustic communication (RemageHealey and Bass, 2010;Remage-Healey and Joshi, 2012).…”
Section: Accepted Manuscriptsupporting
confidence: 69%
“…The transient nature of the T administration mimicked natural-occurring pulses seen in intersexual rodent social encounters (James et al, 2006;Macrides et al, 1975) and in the current study, this pulse inhibited acoustic communication with a novel female within 30 min, which is considered rapid for steroid hormones (Cornil et al, 2012;Remage Healy, 2012;Wu et al, 2001). The precise mechanism through which T is acting cannot be determined in the present study, but recent research has identified intriguing rapid effects of steroid hormones achieved by non-genomic mechanisms (Cornil et al, 2013;Mangiamele and Thompson, 2012), including effects on acoustic communication (RemageHealey and Bass, 2010;Remage-Healey and Joshi, 2012).…”
Section: Accepted Manuscriptsupporting
confidence: 69%
“…GnIH receptor is also expressed in the POA Yin et al, 2005) and PAG . These brain areas are known to regulate aggressive behavior (Absil et al, 2001;Cornil et al, 2012). Because GnIH decreases aggressive behavior in male birds , we hypothesized that GnIH may decrease aggressive behavior of male birds by regulating P450arom activity and neuroestrogen synthesis in the brain.…”
Section: How To Identify Neuropeptide-neurosteroid Interactionmentioning
confidence: 99%
“…Recent findings indicate that E2 synthesis in the hippocampus is regulated by gonadotropinreleasing hormone [111]. Indeed, there is a general agreement on the prompt response of aromatase activity as a consequence of the fast synaptic functions and quick requirement of E2 for brain utilization [112]. Neurotransmitters such as dopamine, glutamate, and GABA modulate aromatase activity and, in turn, E2 may act as a neurotransmitter or neuromodulator [15].…”
Section: Aromatase: the Final Rate-limiting Stepmentioning
confidence: 99%